Health Information Seeking Behavior (HISB) among Malaysian parents of children with Autism Spectrum Disorder (ASD): a conceptual framework / Nora Lina Mohd Hussain ... [et al.] - Mohd Hussain, Nora Lina; Mohamed Shuhidam, Shamila; Bunawan, Ap-azli; Husaini, Haslinda (Faculty of Information Management, 2022)
Autism Spectrum Disorder (ASD) is a form of the developmental condition that has been shown to impact verbal and non-verbal communication and social interaction profoundly. Children with autism typically demonstrate verbal delays, repetitive behaviors, issues with concentration, a lack of desire, and deficiencies in social interaction. However, changes in socioeconomic and demographic sectors provide obstacles for parents with limited health information-seeking behavior (HISB) about their autistic children's health. This paper aims to discuss and propose the conceptual framework of health information-seeking behavior (HISB) among parents of children with autism spectrum disorder (ASD) in Malaysia. The significance of this study may assist the government, NGOs, and autism research center with information for a better understanding of HISB among parents of children with ASD.